The Influence of Influencer Reviews and Electronic Word of Mouth on Purchase Decisions of The Originote Cosmetic Products - Romadani, Tri; Yamini, Era (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
This study aims to examine (1) the influence of influencer reviews on purchasing decisions for the Originote cosmetic products, (2) the influence of electronic word-of-mouth on purchasing decisions for the Originote cosmetic products. The method used in this study is a quantitative approach. Data were collected through the distribution of questionnaires online to 400 respondents who are consumers of the Originote products throughout Indonesia. The sampling technique used a non-probability sampling method with a purposive sampling technique. The data analysis technique used was multiple linear regression. The results of the study indicate that influencer reviews, electronic word-of-mouth, together have a significant effect on purchasing decisions for the Originote cosmetic products. Partially, influencer reviews (X1) have a positive effect on purchasing decisions (Y) for the Originote moisturizer, as can be seen from the calculated t-test of 7.600 > t-table of 1.966, and the significance value is 0.000 ≤ 0.05. Electronic word of mouth (X2) has a positive and significant effect on purchasing decisions (Y) of the Originote cosmetic products, as can be proven from the calculated t value of 3.770 > t table 1.966, and the significance value is 0.000 ≤ 0.05.